Ko se srečata znanje in odločanje: Pristopi k ocenjevanju varnostnih tveganj - Prislan Mihelič, Kaja; Modic, Maja; Lobnikar, Branko; Slak, Boštjan; Mihelič, Anže (University of Maribor Press, 2024)
When Knowledge and Decision-making Meet: Approaches to Security Risk Assessment. Assessing security risks is the cornerstone of strategic security management in developed nations. This monograph provides a broad overview of various orientations and approaches to assessing security risks and vulnerabilities. It encompasses national strategic and legislative frameworks, essential professional resources, international standards, and guidelines. In addition to general orientations, the monograph presents selected practices of foreign countries in assessing security risks and threats. The central contribution of this work lies in the proposed model for assessing threats and risks in the realm of public security, primarily intended for organizations operating in the field of public security. The model is fundamentally comprehensive, cohesive, and practically applicable. Serving as a guiding tool, it is designed for analysts to conduct assessments through an analytical and systematic process, thereby providing decision-makers with appropriate informational support. Due to specific expectations and requirements, the model is presented in both full and short versions.